A Coordinated Communication and Power Management Strategy for DC Converters in Renewable Energy Systems - Feng Zhou; Takahiro Kawaguchi; Seiji Hashimoto; Wei Jiang (Energies)
Effective communication among distributed energy sources (DESs) is essential for optimizing energy allocation across power sources, loads, and storage devices in integrated renewable energy and energy management systems. This paper proposes a novel communication and energy management strategy to address challenges related to communication interference and inefficiencies in energy management. The proposed strategy employs the DC bus as a communication medium, enabling module coordination via pulsed voltage signals. Controller modules regulate the bus voltage based on the energy state of the bus and control the supplementary or absorptive energy flow from slave modules to maintain voltage stability. Simultaneously, communication between the master and slave modules is achieved through pulsed voltage signals of varying pulse widths, and power sharing is realized via droop control. Experimental results demonstrate that the proposed method effectively distributes energy across different voltage levels, enabling the controller modules to precisely regulate the voltage of the slave modules under varying load conditions.